Financial impact of sarcopenia on hospitalization costs - Sousa, Ana (2016)
Sarcopenia is currently defined as a combination of both low muscle mass and low muscle function, according to the European Working Group on Sarcopenia in Older People (EWGSOP). It is estimated that sarcopenia occurs between 5 and 45% of community-dwelling older adults. Although this condition has been mainly described in older adults, it can also be present in younger individuals. Cherin et al. in a study conducted among community-dwelling adults showed that 9% of the individuals aged between 45 and 54 years and 13.5% of those aged from 55 to 64 years were sarcopenic. Previous studies have shown that this condition is highly frequent among hospitalized older patients,610 ranging from 10 to 37.3%, and was identified in circa one-fifth of patients aged under 65 years. This condition has been associated with physical disability, low quality of life and higher mortality in community-dwelling older adults. Among hospitalized patients, sarcopenia has been related with poor clinical outcome, namely worse postoperative outcomes, higher risk of non-elective readmission6 and higher mortality. Although sarcopenia differs from undernutrition, both of these conditions can cause muscle mass and/or strength loss. The main difference between these two conditions is that undernutrition, especially because of starvation, generally reacts to nutrition support, whereas sarcopenia can be refractory to nutritional intervention. Considering the impact of sarcopenia on both communitydwelling and hospitalized individuals, health-care costs of this condition are expected to be high. However, according to our knowledge, data on the economic burden of sarcopenia are limited. One study from 2004, conducted among representative samples of American adults aged 60 years, reported that the estimated health-care cost attributable to sarcopenia defined as the loss of muscle mass was $18.5 billion ($10.8 billion in men, $7.7 billion in women). Recent studies from 2013 and 2015 reported that sarcopenia determined by computed tomography scans was associated with increased costs in major surgery. Nevertheless, the impact of sarcopenia on hospitalization costs among a wider variety of patients, from surgical and medical wards, remains to be documented. Considering the adverse consequences sarcopenia entails among hospitalized patients and the financial constraints that health-care systems often face, it is important to recognize and explore the association of sarcopenia with hospitalization costs, to maximize resources and provide a more effective health-care plan. Therefore, the present study aims to increase the knowledge on the association of sarcopenia with costs among a wide-ranging sample of adult hospitalized patients